HUBUNGAN ANTARA PENGETAHUAN IBU TENTANG KARIES DENGAN UPAYA PEMELIHARAAN KESEHATAN GIGI ANAK DI POSYANDU BINAAN PUSKESMAS CITALEM DESA SUKAMULYA KECAMATAN CIPONGKOR KABUPATEN BANDUNG BARAT (Jurnal Terapi Gigi dan Mulut, 2022)
Mother's efforts in maintaining the dental health of children from an early age can affect children's habits in maintaining dental health. This study aims to determine the relationship between mom's knowledge of caries and children's dental health care efforts at Posyandu Binaan Puskesmas Citalem Desa Sukamulya Kecamatan Cipongkor Kabupaten Bandung Barat. this type of research is analytical research, the research design used is cross sectional using a questionnaire. The sampling technique was purposive sampling and there were 84 respondents as research subjects. The results of the chi-square test show that the p-value of the relationship between maternal knowledge about caries and efforts to maintain children's dental health is 0.5,90. Conclusion: there is no relationship between mom's knowledge of caries and children's dental health care efforts at Posyandu Binaan Puskesmas Citalem Desa Sukamulya Kecamatan Cipongkor Kabupaten Bandung Barat (p-value > 0.05).